278 Gynaecologic and non-gynaecologic tumors metastatic to the ovaries. (4th December 2020) - Ziyadova, Gunel; Salman, Mehmet Coskun; Gultekin, Murat; Ozgul, Nejat
Abstract : Introduction/Background: The ovaries are a frequent site of metastasis and tumors metastatic to the ovaries account for 5–6% of all ovarian tumors. In most cases, the primary tumor originates from gastrointestinal tract, breast, and gynaecologic organs including endometrium and cervix. The diagnosis is often made on final pathology since many metastatic tumors mimics primary ovarian carcinoma and most patients present with pelvic mass. Therefore, surgery is the mainstay of management. The prognosis of patients with ovarian metastasis is generally poor. However, survival rates are even worse in patients with non-gynaecologic primaries. Methodology: Patients with pelvic mass who were operated at Hacettepe University Faculty of Medicine, Department of Obstetrics and Gynaecology for a five-year period were identified. Among them, the clinical and pathological characteristics of patients with tumors metastatic to the ovaries were retrospectively reviewed. Survival analysis was done as well with a particular focus on the origin of the primary tumor. Results: Tumors metastatic to the ovaries accounted for 16.2% of all ovarian malignancies and 79 cases with ovarian metastases constituted the study group. Mean age of the patients was 56.3 years. Primary tumor non-gynaecologic in 65.8% of cases and colon cancer was the most common non-gynaecologic primary followed by stomach and breast cancer. All remaining patients (34.2%) had primary endometrial cancer metastatic to the ovaries. Patients with gynaecologic primaries were significantly older, but the levels of tumor markers were similar. Patients with non-gynaecologic primaries most-commonly presented with abnormal imaging results and pain while abnormal bleeding was the most common symptom in those with gynaecologic primaries. Staging surgery and total abdominal hysterectomy with bilateral salpingo-oophorectomy were the most common surgeries performed. Bilateral ovarian involvement was detected in 62.0% of cases. Mean diameter of the tumor was 6.5 cm. Adjuvant treatment was given in 96.2% of patients. Of patients, 43.0% died of disease. Median survival was 19.7 months, but this was significantly longer in patients with non-gynaecologic primaries (10.0 months vs 32.6 months, p=0.05). Longest survival was detected in patients with colon cancer. Extent of surgery or the type of adjuvant therapy given did not affect median survival. Conclusion: Tumors metastatic to the ovaries account for a significant proportion of all ovarian cancers. Most of these tumors are diagnosed in elderly patients and prognosis is relatively poor regardless of the surgical procedures performed and adjuvant therapies given. Disclosures: No potential conflict of interest to declare.